Children and the Good Life
VIII, 208 p.
Keywords: Today, the challenge for Research on Children is the issue of the "good life". Discourses and the production of knowledge on the "good life" require a theoretical frame. This frame can be provided by various perspectives: the feminist ethic of care, the Human and Children's Rights Convention, the idea of welfare, or the Capability Approach. The aim of this book is to answer the question of how we can define and measure a "good life" for children growing up in the modern world. The book discusses the cogency of universalistic theories and explores the potential contribution of research on children and the possible integration of children into the research process and debates on the "good life". The articles collected in this book reflect the state of the art in research and discussions on this topic. Written by researchers from different countries and with expertise in various disciplines, the articles present theoretical and methodological analyses as well as empirical reports.